Răspuns :
.a)1/6y+1/4y=(1/6y+1/4y)=5/12y
b)-2/7x+3/7x=(−2/7x+3/7x)=1/7x
c)-3/8x-11/4x=−3/8x+−11/4x=(−3/8x+−11/4x)=−25/8x
d)3/√2a+5/√2a=5.656854*a=5.656854a
e)55/√3a−2/√3a=30.599564*a=30.599564a
f)−8−8/√5c+5/√5c=−1.341641c−8
2.a)-3x-2y+7x-3y=−3x+−2y+7x+−3y=(−3x+7x)+(−2y+−3y)=4x+−5y
b)5xy+6 x^{2}=6x2+5xy
y-4x^{2}=y+−4x2 =−4x2+y
y-6xy=y+−6xy=−6xy+y
c)7+2 x^{2}=2x2+7
-5+8 x^{2} -2=−5+8x2+−2=(8x2)+(−5+−2)=8x2+−7
d)2,(3) x^{2} -3,(2) y^{2} +4,(1) y^{2} -4,(5) x^{2}=6x2+−6y2+4y2+−20x2=(6x2+−20x2)+(−6y2+4y2)=−14x2+−2y2=−14x2−2y2
e)3,25xy+5,5x^{2} -2,7xy-6,7x^{2}=325xy+55x2+−27xy+−67x2=(55x2+−67x2)+(325xy+−27xy)=−12x2+298xy
g)3√2x2−5√3x+2√6−2√2x2+7√3x−2√6=1.414214x2+3.464102x
h)x2(2√3+5)−x(3√2−1)+5√2−x2(2√3−3)+x(2√2+3)−5√2=8x2+2.585786x
3.a)9 x^{2} -3 x^{3} +4x-7 x^{2} +5 x^{3} -8x=9x2+−3x3+4x+−7x2+5x3+−8x=(−3x3+5x3)+(9x2+−7x2)+(4x+−8x)=2x3+2x2+−4x
b)-2/7x+3/7x=(−2/7x+3/7x)=1/7x
c)-3/8x-11/4x=−3/8x+−11/4x=(−3/8x+−11/4x)=−25/8x
d)3/√2a+5/√2a=5.656854*a=5.656854a
e)55/√3a−2/√3a=30.599564*a=30.599564a
f)−8−8/√5c+5/√5c=−1.341641c−8
2.a)-3x-2y+7x-3y=−3x+−2y+7x+−3y=(−3x+7x)+(−2y+−3y)=4x+−5y
b)5xy+6 x^{2}=6x2+5xy
y-4x^{2}=y+−4x2 =−4x2+y
y-6xy=y+−6xy=−6xy+y
c)7+2 x^{2}=2x2+7
-5+8 x^{2} -2=−5+8x2+−2=(8x2)+(−5+−2)=8x2+−7
d)2,(3) x^{2} -3,(2) y^{2} +4,(1) y^{2} -4,(5) x^{2}=6x2+−6y2+4y2+−20x2=(6x2+−20x2)+(−6y2+4y2)=−14x2+−2y2=−14x2−2y2
e)3,25xy+5,5x^{2} -2,7xy-6,7x^{2}=325xy+55x2+−27xy+−67x2=(55x2+−67x2)+(325xy+−27xy)=−12x2+298xy
g)3√2x2−5√3x+2√6−2√2x2+7√3x−2√6=1.414214x2+3.464102x
h)x2(2√3+5)−x(3√2−1)+5√2−x2(2√3−3)+x(2√2+3)−5√2=8x2+2.585786x
3.a)9 x^{2} -3 x^{3} +4x-7 x^{2} +5 x^{3} -8x=9x2+−3x3+4x+−7x2+5x3+−8x=(−3x3+5x3)+(9x2+−7x2)+(4x+−8x)=2x3+2x2+−4x